The Response of the Functional Traits of Phragmites australis and Bolboschoenus planiculmis to Water and Saline–Alkaline Stresses - Lili Yang; Yanjing Lou; Zhanhui Tang (Plants)
Soil saline–alkaline stress and water stress, exacerbated by anthropogenic activities and climate change, are major drivers of wetland vegetation degradation, severely affecting the function of wetland ecosystems. In this study, we conducted a simulation experiment with three water levels and four saline–alkaline concentration levels as stress factors to assess eight key functional traits of Phragmites australis and Bolboschoenus planiculmis, dominant species in the salt marsh wetlands in the western region of Jilin province, China. The study aimed to evaluate how these factors influence the functional traits of P. australis and B. planiculmis. Our results showed that the leaf area, root biomass, and clonal biomass of P. australis significantly increased, and the leaf area of B. planiculmis significantly decreased under low and medium saline–alkaline concentration treatments, while the plant height, ramet number, and aboveground biomass of P. australis and the root biomass, clonal biomass, and clonal/belowground biomass ratio of B. planiculmis were significantly reduced and the ratio of belowground to aboveground biomass of B. planiculmis significantly increased under high saline–alkaline concentration treatment. The combination of drought conditions with medium and high saline–alkaline treatments significantly reduced leaf area, ramet number, and clonal biomass in both species. The interaction between flooding water level and medium and high saline–alkaline treatments significantly suppressed the plant height, root biomass, and aboveground biomass of both species, with the number of ramets having the greatest contribution. These findings suggest that the effects of water levels and saline–alkaline stress on the functional traits of P. australis and B. planiculmis are species-specific, and the ramet number–plant height–root biomass (RHR) strategy may serve as an adaptive mechanism for wetland clones to environmental changes. This strategy could be useful for predicting plant productivity in saline–alkaline wetlands.